Effect of Tembotrione on Weed Growth and Productivity of Kharif Maize (Zea mays L.) - Sharma, Puscal; Duary, B.; Aktar, S. N.; Jaiswal, D. K.; Bishoyi, B. S. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in maize (Zea mays L.) during both kharif (June–September, 2014 and 2015) seasons in a randomized block design with nine treatments, including the herbicide tembotrione as early post-emergence at 80, 100 and 120 g ha-1 both as sole and in combination with atrazine at 500 g ha-1, atrazine at 1000 g ha-1, hand-weeding twice at 25 and 40 DAS and unweeded control with three replications. The experimental field was heavily infested with Ludwigia parviflora (Jacq.) Raven, Cynodon dactylon (L.) Pers., Cyperus rotundus (L.) and Fimbristylis miliacea (L.) Vahl. The yield of maize was reduced by around 48% due to weed infestation. From the experiment, it was found that combined application of tembotrione and atrazine was much more effective than sole application of herbicide at any of the levels that were evaluated. Tembotrione at a rate of 80–100 g ha-1+stefesmero surfactant at 733 g ha-1+atrazine at 500 g ha-1 recorded the lowest weed density, weed biomass and weed index; highest values of growth and yield parameters as well as the yield of maize. Therefore, early post–emergence application of tembotrione at 80–100 g ha-1+stefesmero surfactant at 733 g ha-1+atrazine 500 g ha–1 appeared to be the most effective weed management approach for higher weed control efficiency, yield, gross and net return of kharif maize in lateritic soil of West Bengal.